DEVELOPMENT OF LEARNING COMIC ANIMATION MEDIA BASED ON PORTABLE ISPRING APPLICATION OF LIGHT PROPERTIES TO IMPROVE SCIENCE LITERACY - Nurharini, Firdausi; Minarno, Eko Budi; Utami, Ulfah (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This development research aims to overcome the problems of students who are technologically literate but have not been able to use technology for useful things, the As-salam school has provided science media but it does not attract students' interest to learn it, there are no teaching materials that can guide students effectively. effective. especially to improve scientific literacy skills. The development of this animated comic uses the 2015 Dick and Carey development model which has 10 stages. The object of the research assessment consisted of content expert validators, design expert validators, learning expert practitioners, and fourth-grade students.The results are: (1)The specification of learning media in the form of comic animation online animated comic media and offline (portable). Animated comic media that can be accessed on mobile phones, iPhones, tablets, and computers. In the learning media, animated comics contain activities such as exercises, graphing, and drawing; (2) The use of comic animation learning media is done through online learning; (3) The results of research media learning comic animation to improve the ability of scientific literacy. The level of validity has 100% design validity (very valid), 71% validity of the material/content (valid), practicality shows 97% and 85% practicality of learning (very practical), and the effectiveness of the trial strategy (One To One) has 97% (Very appropriate), small group evaluation trials show of 99% (Very appropriate), field evaluation trials show of 99.6% (Very appropriate). The effectiveness level of using an Independent sample t-test / one group pre-test post-test to test the hypothesis, based on calculations obtained thitung = 4,456 and ttabel = 1,710 so that thitung = 4.456> ttabel = 1,710 H0 is rejected and H1 is accepted. So it can be concluded that learning media proved to be significantly effective.